CURRENT USE AND OUTCOMES OF CELLULAR THERAPY: BRAZILIAN SUMMARY SLIDES -2025 ‎ - Cinthya Corrêa da Silva; Anderson João Simione; Paula Moreira da Silva Sabaini; Antonio Vaz Macedo; Heliz Regina Alves das Neves; Monique Ammi; Flavia Ferreira da Costa; Celso Arrais Rodrigues; Adriana Mendes de Quadros Cavilha; Rosana Rocha Concilio; Phillip Scheinberg; Nelson Hamerschlak; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Chimeric antigen receptor T-cells (CAR T cells) are genetically modified cellular immunotherapies approved as a standard of care treatment for patients with lymphoma and leukemia worldwide. Here, we report the initial activity in Brazilian centers through the collaboration between the Brazilian Cellular Therapy and Bone Marrow Transplant Society (SBTMO) and the Center for International Blood and Marrow Transplant Research (CIBMTR). A total of 104 patients who received commercial and academic CAR-T cells in Brazil between January 2020 and April 2025 were included. The median age was 56 years (range 4-83). Indications were Non-Hodgkin Lymphoma (NHL; 75 cases; 72%), Acute Lymphoblastic Leukemia (ALL; 23 cases; 22%), Multiple Myeloma (MM; 4 cases; 4%) and Chronic lymphoblastic leukemia (CLL; 2 cases; 2%). Anti-CD19 commercial CAR-T were 82% of the total, 68 for NHL and 17 for ALL). Most deaths were due to disease progression or relapse (n=19), followed by infections (n=8). The overall survival after a median follow-up of 200 days was 73% (95% CI: 62-86; N=63) for NHL and 79% (95% CI: 63-99; N=19) for ALL. This report demonstrates the successful initial implementation of CAR-T cells in Brazil among centers that report to the SBTMO/CIBMTR. This infrastructure will assist in further capturing the activity, assessing the outcomes, and complying with regulatory requirements.